Diabetes through the ages - Hall, Michael Stephen (Henry Stewart Talks, 2013)
Searching for the cause of diabetes, Diabetes in 19th century, The islet cells in the pancreas, Edouard Laguesse, Oscar Minkoski and J. von Mering, Sir Edward Albert Sharpey-Schafer, Eugene Opie, George Ludwig Zuelzer, Ernest Lyman Scott, Nicolae Paulescu, J.J.R. Macleod, C. H. Best and F. G. Banting: their research and story of discovering insulin, James B. Collip, Leonard Thompson, Manufacturing insulin, The famous case Elizabeth Hughes, Insulin around the world, Dr. R. D. Lawrence, Dr. Ernesto Roma, Life for a child programme
Archived at 2023/04/30